Paradoxical role of reactive oxygen species in bone remodelling: implications in osteoporosis and possible nanotherapeutic interventions - Largee Biswas; Karishma Niveria; Anita Kamra Verma (Open Exploration Publishing Inc., 2022)
Osteoporosis is a metabolic bone disorder that affects both sexes and is the most common cause of fractures. Osteoporosis therapies primarily inhibit osteoclast activity, and are seldom designed to trigger new bone growth thereby frequently causing severe systemic adverse effects. Physiologically, the intracellular redox state depends on the ratio of pro-oxidants, oxidizing agents (reactive oxygen species, ROS) and antioxidants. ROS is the key contributor to oxidative stress in osteoporosis as changes in redox state are responsible for dynamic bone remodeling and bone regeneration. Imbalances in ROS generation vs. antioxidant systems play a pivotal role in pathogenesis of osteoporosis, stimulating osteoblasts and osteocytes towards osteoclastogenesis. ROS prevents mineralization and osteogenesis, causing increased turnover of bone loss. Alternatively, antioxidants either directly or indirectly, contribute to activation of osteoblasts leading to differentiation and mineralization, thereby reducing osteoclastogenesis. Owing to the unpredictability of immune responsiveness and reported adverse effects, despite promising outcomes from drugs against oxidative stress, treatment in clinics targeting osteoclast has been limited. Nanotechnology-mediated interventions have gained remarkable superiority over other treatment modalities in regenerative medicine. Nanotherapeutic approaches exploit the antioxidant properties of nanoparticles for targeted drug delivery to trigger bone repair, by enhancing their osteogenic and anti-osteoclastogenic potentials to influence the biocompatibility, mechanical properties and osteoinductivity. Therefore, exploiting nanotherapeutics for maintaining the differentiation and proliferation of osteoblasts and osteoclasts is quintessential.